Asked
9 months ago

Viewed
360324 times

Answer: y=-3x-7

Step-by-step explanation:

Y+1 =-3x-6

**Answer:**

y=-3x+5

**Step-by-step explanation:**

1. Put the equation into point-slope form: y-y1=m(x-x1)

Use the coordinates to put into y1 and x1 and use the slope to put into m. For y1 and x1, whenever there's a negative number in the provided coordinates, you'll need to change the subtraction sign into an addition sign because two negatives make a positive.

y+1=-3(x-2)

2. Distribute -3 to x-2 and subtract 1 from both sides.

y+1=-3x+6

y=-3x+5

Enter your username or email to reset your password. You will receive an email with instructions on how to reset your password. If you are experiencing problems resetting your password contact us or send us an email